Faktor Faktor yang Berhubungan dengan Kesehatan Reproduksi Remaja di Posyandu Remaja Desa Sumber Sari Wilayah Kerja UPTD Puskesmas Toto Rejo Kabupaten Oku Timur Tahun 2023 - Diana Oktarina; Sabtian Sarwoko; Yudi Budianto (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Introduction: Report Global School Health Survey (GSHS) shows that 3.3% of teenagers aged 15-19 years suffer from AIDS, only 9.9% of women and 10.6% of men aged 15-19 years have in-depth knowledge about HIV/AIDS and 0.7% of women and 4.5% of men have had premarital sex. Goal: KnowFactors Associated with Adolescent Reproductive Health in the Youth Posyandu, Sumber Sari Village, Toto Rejo Community Health Center Working Area, East Oku Regency. Method: The research design used isCross Sectional. The population in this study were 65 teenagers aged 10-19 years in Sumber Sari village. Sampling technique by means of accidental sampling namely as many as 65 teenagers. This research was conducted in May-June 2023. Data analysis techniques, namelyWho – Square. Results: research shows that there is a relationship between socio-economic factors (p=0.020) and biological factors (0.020) on adolescent reproductive health at the youth Posyandu in Sumber Sari village, working area of ??Toto Rejo Community Health Center, East Ogan Komering Ulu (OKU) Regency in 2023 and No relationshipCultural and environmental factors (0.588) and psychological factors (0.827) on adolescent reproductive health at the youth Posyandu in Sumber Sari village, working area of ??Toto Rejo Health Center, East OKU Regency in 2023.